Reparations and Restitution Justice for Colonial Crimes - Taku, Charles A (Comparative and International Law Journal of Southern Africa, 2024)
This paper demonstrates that communities and victims of colonial crimes who suffered gross violations of international human rights and serious violations of international humanitarian law are entitled to reparations and the restitution of their stolen or looted African cultural heritage. Requests made by victims and succeeding generations for reparations and restitution have not been seared into the conscience of humanity. Atrocity crimes against Africans were committed under the cloth of legality. The international legal order which enabled the atrocity crimes did not consider Africans as subjects of international law. Colonial and supposed independent African neo-colonial states were established without effective political, economic and legal frameworks for reparations and restitution justice. This paper establishes a factual, historical and legal basis for reparations for historical crimes against Africans and the restitution of stolen African cultural heritage.